2022
DOI: 10.3390/biom12091170
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SARS-CoV-2 RBD Mutations on the Production of a Recombinant RBD Fusion Protein in Mammalian Cells

Abstract: SARS-CoV-2 receptor-binding domain (RBD) is a major target for the development of diagnostics, vaccines and therapeutics directed against COVID-19. Important efforts have been dedicated to the rapid and efficient production of recombinant RBD proteins for clinical and diagnostic applications. One of the main challenges is the ongoing emergence of SARS-CoV-2 variants that carry mutations within the RBD, resulting in the constant need to design and optimise the production of new recombinant protein variants. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…Thus, the immunogenicity of 2omRBD‐Fc protein is also suboptimal. It is reported that the E484K mutation in RBD interferes with the proper disulphide‐bond formation and folding of the B.1.351 RBD‐Fc fusion protein, resulting in the reduction of its thermostability 54 . We speculate that similar structural alterations also occurred in 2omRBD‐Fc as the Omicron strains contain E484A mutation, therefore contributed to its low immunogenicity.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Thus, the immunogenicity of 2omRBD‐Fc protein is also suboptimal. It is reported that the E484K mutation in RBD interferes with the proper disulphide‐bond formation and folding of the B.1.351 RBD‐Fc fusion protein, resulting in the reduction of its thermostability 54 . We speculate that similar structural alterations also occurred in 2omRBD‐Fc as the Omicron strains contain E484A mutation, therefore contributed to its low immunogenicity.…”
Section: Discussionmentioning
confidence: 72%
“…It is reported that the E484K mutation in RBD interferes with the proper disulphide-bond formation and folding of the B.1.351 RBD-Fc fusion protein, resulting in the reduction of its thermostability. 54 We speculate that similar structural alterations also occurred in 2omRBD-Fc as the Omicron strains contain E484A mutation, therefore contributed to its low immunogenicity. Thus, further optimization of omicron-derived antigens, or utilizing other VOC antigens with high immunogenicity, may enhance the immune responses induced by sequential immunization.…”
Section: F I G U R E 4 (See Caption On Next Page)mentioning
confidence: 70%
“…Preclinical studies have shown that RBD-Fc-based vaccines are effective [ [5] , [6] , [7] ], and clinical research are currently underway. In addition, different platforms were used to generate RBD-based recombinant proteins, including yeast [ 8 ], mammalian cells [ 9 , 10 ], and plants [ 11 , 12 ]. Plant expression systems offer several advantages for recombinant protein biosynthesis.…”
Section: Introductionmentioning
confidence: 99%